Connectivity and Nitrate Uptake Potential of Intermittent Streams in the Northeast USA - Addy, Kelly; Gold, Arthur J.; Welsh, Molly K.; August, Peter V.; Stolt, Mark H.; Arango, Clay P.; Groffman, Peter M. (Frontiers in Ecology and Evolution, 2019)
Non-perennial streams dominate the extent of stream networks worldwide. Intermittent streams can provide ecosystem services to the entire network – including nitrate uptake to alleviate eutrophication of coastal waters – and are threatened by lack of legal protection. We examined 12 intermittent streams in the temperate, humid climate of the Northeast USA. Over three years of monitoring, continuous flow was observed a median of 277 d yr-1, with no-flow conditions from early summer into fall. Estimated median discharge was 2.9 L s-1 or 0.36 mm d-1. All intermittent streams originated from source wetlands (median area: 0.27 ha) and the median length of the intermittent stream from the source wetland to the downstream perennial stream was 344 m. Through regional geospatial analysis with high resolution orthophotography, we estimated that widely available, “high resolution” (1:24,000) hydrography databases (e.g., NHDPlus HR) only displayed 43% of the total number of intermittent streams. Whole-stream gross nitrate-N uptake rates were estimated at six intermittent streams during continuous flow conditions using pulse additions of nitrate and a conservative tracer. These rates displayed high temporal variability (range: no detect to over 6000 mg N m-1 d-1); hot moments were noted in nine of the 65 pulse additions. Whole-stream gross nitrate-N uptake rates were significantly inversely related to discharge, with no measurable rates above 7 L s-1. Temperature was significantly positively correlated with whole-stream gross nitrate-N uptake rates, with more hot moments in the spring. Microbial assays demonstrated that nitrate cycling in intermittent streams are consistent with results from low order, perennial forested streams and highlighted the importance of debris dams and pools – potential locations for transient storage. Our assessment suggests that intermittent streams in our region may annually contribute 24-47% of the flow to perennial streams and potentially remove 4.1 to 80.4 kg nitrate-N km-2 annually. If development in these areas continues, perennial streams are in danger of losing a portion of their headwaters and potential nitrate uptake areas may become nitrate sources to downstream areas. These results argue to manage fluvial systems with a holistic approach that couples intermittent and perennial components.